Aspects Regarding Ecumenical and Christian Relations of the Greek Catholic Clergy from the Eparchy of Oradea in the Twentieth Century - SANA, Silviu-Iulian (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2026)
Based on a specialized bibliography, the present study highlights – both theologically and historically – some important moments of fraternity and communion, of a real ecumenism, between Christians of different confessions in the territory of Transylvania and Partium both during the Second Vienna Arbitration of Hungary (1940–1944) and, especially, during the period of communist Romania. Special attention is paid to the Greek Catholic clergy and their actions, namely the publication – with the consent of the Holy Apostolic See of Rome – of the First Ecumenical Prayer, the ecumenical funeral service for the victims of the June 1944 bombing in Oradea, and Bishop Iuliu Hirțea’s practice of ecumenism in prison. The first part of the work discusses the most important document of the Magisterium of the Catholic Church that addresses ecumenism, specifically parts of the text of the Second Vatican Council that define the concept of ecclesiastical unity and introduce the reader to the depth of the ecumenical message of the text. Thus, important theological themes in the theology of ecumenism are discussed such as: the perfection of communion, regret, the desire for union, respect, brotherly love, ecumenical work, Christian values, common heritage, the life of others, the shedding of blood. The second part briefly exemplifies the presence of the two Romanian church leaders (Greek Catholic and Orthodox) at the official visit of Regent Miklós Horthy to Cluj in September 1940. The printing of a special prayer to be read by the priest before the faithful during the week of Christian unity in 1942 represents an important step taken by the Greek Catholics – of course, with the approval of Rome – on the difficult path of reconciliation between Christians. The text continues with concrete aspects of Christian solidarity during the war and communist persecution, letting history – both from the archival documents and from the memoirs of the time – speak. A young Orthodox believer, Cornel Onaca, spoke about the real ecumenism of Greek Catholic priests, who, in addition to learning and assisting in their prayers, praised the gestures of Christian charity they made in helping all those in need – about an exemplary priest and about his “holy courage”, namely about Bishop Iuliu Hirțea, Matei Boilă, who was incarcerated together with the bishop of Oradea in Jilava Prison. Focused on the period after 1990, the study presents very briefly the ecumenical meetings of the Week for Christian Unity held at the Greek Catholic parishes of Oradea, as well as the ecumenical celebration of the blessing of the waters (on the Crișul Repede River) by Bishop Virgil Bercea and the Orthodox Bishop Sofronie Drincec.